2006
DOI: 10.1038/sj.mp.4001893
|View full text |Cite
|
Sign up to set email alerts
|

Valproate protects dopaminergic neurons in midbrain neuron/glia cultures by stimulating the release of neurotrophic factors from astrocytes

Abstract: Valproate (VPA), one of the mood stabilizers and antiepileptic drugs, was recently found to inhibit histone deacetylases (HDAC). Increasing reports demonstrate that VPA has neurotrophic effects in diverse cell types including midbrain dopaminergic (DA) neurons. However, the origin and nature of the mediator of the neurotrophic effects are unclear. We have previously demonstrated that VPA prolongs the survival of midbrain DA neurons in lipopolysaccharide (LPS)-treated neuron-glia cultures through the inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
242
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(257 citation statements)
references
References 58 publications
(68 reference statements)
11
242
1
3
Order By: Relevance
“…cells and other cellular models of midbrain DA neurons in vitro (Chen et al 2006;Chen et al 2007;Collins et al 2015;Gardian et al 2004;Kidd and Schneider 2010;Kidd and Schneider 2011;Kontopoulos et al 2006;Outeiro et al 2007;St Laurent et al 2013;Wu et al 2008;Zhu et al 2014). However, to our knowledge, the present study is the first to show that a selective HAT activator can induce similar neurotrophic effects in the SH-SY5Y neuronal cell line.…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of mentioning
confidence: 51%
See 1 more Smart Citation
“…cells and other cellular models of midbrain DA neurons in vitro (Chen et al 2006;Chen et al 2007;Collins et al 2015;Gardian et al 2004;Kidd and Schneider 2010;Kidd and Schneider 2011;Kontopoulos et al 2006;Outeiro et al 2007;St Laurent et al 2013;Wu et al 2008;Zhu et al 2014). However, to our knowledge, the present study is the first to show that a selective HAT activator can induce similar neurotrophic effects in the SH-SY5Y neuronal cell line.…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of mentioning
confidence: 51%
“…We and others have shown that pan-and class-specific HDAC inhibitors can protect DA neurons (Chen et al 2006;Chen et al 2007;Collins et al 2015;Gardian et al 2004;Kidd and Schneider 2010;Kidd and Schneider 2011;Kontopoulos et al 2006;Outeiro et al 2007;St Laurent et al 2013;Wu et al 2008;Zhu et al 2014) and sympathetic neurons (Collins et al 2015) in experimental models of PD. The potential of this approach for clinical translation is highlighted by an ongoing Phase I clinical trial of the FDA-approved drug Glycerol Phenylbutyrate (a HDAC inhibitor) which is exploring the potential of this drug to increase the removal of α-synuclein from the brain (NCT02046434) (for recent reviews see Harrison and Dexter 2013;Schneider et al 2013;Valor et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in Drosophila, toxic nuclear aggregates of α-synuclein interact with histone H3 and promote its deacetylation, possibly through a histone-"masking" mechanism [104]. Consistent with this result, several studies targeting HDAC members through sodium butyrate or valproic acid have shown an increase in histone acetylation, associated with prosurvival and anti-inflammatory effects, and decreased neurotoxicity markers [105][106][107][108][109][110].…”
Section: Pdmentioning
confidence: 73%
“…In contrast, Castro et al (2005) reported significant concentration-dependent increases in GDNF mRNA expression in C6 cells after treatment with VPA for 48 h, but not for 24 h. These discrepancies can be due to different time-courses for the induction of the two neurotrophic factors or to differences in the models used (Castro et al, 2005). Moreover, VPA pre-treatment protects midbrain dopaminergic neurons against LPS-or MPP + -induced toxicity (Chen et al, 2006b). VPA-induced survival of midbrain dopaminergic neurons in LPS-treated neuronglia cultures involves the inhibition of the release of proinflammatory factors from microglia (Peng et al, 2005).…”
Section: Anti-depressants Anti-psychotics and Mood Stabilizersmentioning
confidence: 99%